(untitled) (Global Journal of Human-Social Science, 2014)
Grameen Motsho O Pashusampad (Fisheries and Livestock) Foundation (GMPF)-is a sister organization of Grameen Bank (GB) involves in livestock and fish culture, mobilizing poor people engage